Study of English as an additional language in students with dyslexia - Maria Vilanova Cifre; Lluís Barceló Coblijn (Language and Health)
This paper examines the difficulties dyslexic students encounter while learning English as a foreign language. It is not only about stating that dyslexic students have problems when learning a foreign and opaque language as English, but also about finding out where the difficulties rely on. According to some researchers, English spelling is an ‘opaque’ language that causes difficulties due to its consonant clusters and its complex syllabic structures. The main aim of this essay is to discover the difficulties Catalan speakers encounter when learning this language. Throughout this paper, there is an identification of the main characteristics of Catalan dyslexic students within English learning. This experimental proposal is aimed at analysing the effects of this reading disorder when learning a foreign language with the methodology of participants taking two tests: in English and in Catalan. Each test contains four different activities: a line rhyming exercise, choosing the right option, fill in the gap and dictation. By doing this, it seeks to demonstrate the most complicated groups of consonant clusters for dyslexic students: the ones representing more than one sound in the same letter, thus opaque clusters. Furthermore, due to this opacity, English activities were more significant in terms of results than Catalan exercises.